Kur’ an üslubunda lafzi tekrarlar - Baş, Erdoğan (My University, 2000)
Hadislerde tekrar gerçeği, tekrar-belâgat, tekrar-Nahiv, tekrar-i'câz ilişkisi incelenmiş; tekrarlar üslûp bakımından değerlendirmeye tabi tutulmuş ve tekrarların genel sebepleri izah edilmiştir. Bu bölüm daha ziyade tezin teorik ve teknik kısmını teşkil etmekte; ikinci bölüm ise ekseriyetle pratik alanı kapsamaktadır. İkinci bölümde lâfzî tekrarların açılımı yapılmış; lâfız tekrarları tasnif edilerek incelemeye tabi tutulmuştur. Bu bölüm başlığı altında bir âyet içerisinde tekrarlanan lâfızlar, ardışık âyetlerde vuku bulan tekrarlar ve mükerrer âyetler tetkik edilmiştir.

Thesis is consisting of an introduction and two chapters. In the introduction is defined the frameworks of the matter, the classification and critics of sources, the concept of the tekrar (repetition) and the other concepts that mean the same meaning with tekrar. In the first chapter is studied the elements that help to understand the literal repetition. In this chapter is examined the characteristics of repetition in the Arap litrature, the connection of repetition with eloquence, syntax or grammer (Nahiv), miracle of the Qur'an and repetitions are examined in front of the style and the general reasons of repetition are explained. This first section generally contains the theorical and tecnical area of thesis and the second section, in general, is ibout practical subjects. In the second chapter is studied the usage of the literal repetition and literal repetition is examined by classification. In this chapter is also examined the literal repetitions that repeated in an âyat and the repetitions that follow each other and the repeated âyats.
Keywords: İSLAM DİNİ-KUR’AN; Kur’an-ı Kerim